Phenotypic diversity in an international Cure VCP Disease registry - Chiseko Ikenaga; Andrew R. Findlay; Michelle Seiffert; Allison Peck; Nathan Peck; Nicholas E. Johnson; Jeffrey M. Statland; Conrad C. Weihl (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Dominant mutations in valosin-containing protein (VCP) gene cause an adult onset inclusion body myopathy, Paget’s disease of bone, and frontotemporal dementia also termed multisystem proteinopathy (MSP). The genotype-phenotype relationships in VCP-related MSP are still being defined; in order to understand this better, we investigated the phenotypic diversity and patterns of weakness in the Cure VCP Disease Patient Registry. Methods Cure VCP Disease, Inc. was founded in 2018 for the purpose of connecting patients with VCP gene mutations and researchers to help advance treatments and cures. Cure VCP Disease Patient Registry is maintained by Coordination of Rare Diseases at Sanford. The results of two questionnaires with a 5-point Likert scale questions regarding to patients’ disease onset, symptoms, and daily life were obtained from 59 participants (28 males and 31 females) between June 2018 and May 2020. Independent of the registry, 22 patients were examined at the Cure VCP Disease annual patient conference in 2019. Results In the questionnaires of the registry, fifty-three patients (90%) reported that they were with inclusion body myopathy, 17 patients (29%) with Paget’s disease of bone, eight patients (14%) with dementia, two patients (3%) with amyotrophic lateral sclerosis, and a patient with parkinsonism. Thirteen patients (22%) reported dysphagia and 25 patients (42%) reported dyspnea on exertion. A self-reported functional rating scale for motor function identified challenges with sit to stand (72%), walking (67%), and climbing stairs (85%). Thirty-five (59%) patients in the registry answered that their quality of life is more than good. As for the weakness pattern of the 22 patients who were evaluated at the Cure VCP Disease annual conference, 50% of patients had facial weakness, 55% had scapular winging, 68% had upper proximal weakness, 41% had upper distal weakness, 77% had lower proximal, and 64% had lower distal weakness. Conclusions The Cure VCP Disease Patient Registry is useful for deepening the understanding of patient daily life, which would be a basis to develop appropriate clinical outcome measures. The registry data is consistent with previous studies evaluating VCP patients in the clinical setting. Patient advocacy groups are essential in developing and maintaining disease registries.